Diagnostic Accuracy of Transabdominal Ultrasound and Computed Tomography in Chronic Pancreatitis: A Head-to-Head Comparison - Nordaas, Ingrid Kvåle; Engjom, Trond; Gilja, Odd Helge; Havre, Roald Flesland; Sangnes, Dag André; Haldorsen, Ingfrid S.; Dimcevski, Georg (Ultrasound International Open, 2021)
Purpose Computed tomography (CT) is the most used imaging modality for diagnosing chronic pancreatitis (CP), but advances in transabdominal ultrasound (US) technology have given US a position as a viable alternative. We aimed to evaluate the diagnostic accuracy of abdominal CT and pancreatic US compared to the reference standard, a modified Mayo score.Materials and Methods CT, US, and endoscopic ultrasound (EUS) were performed in patients referred due to suspected CP. The modified Mayo score included EUS results, clinical presentation, and results from exocrine and endocrine pancreatic function tests. We scored CT findings according to the modified Cambridge classification and US findings according to the Rosemont classification.Results In total, 73 patients were included. 53 patients (73%) were categorized as CP and 20 (27%) as non-CP. CT and US yielded similar sensitivities (68% and 64%, respectively) and specificities (75 and 85%, respectively) and similar areas under the receiver operating characteristic curves for diagnosing CP. We found no significant differences between the areas under the receiver operating characteristic curves (AUROCs) for CT (AUROC 0.75, 95% CI 0.63–0.87) and US (AUROC 0.81, 95% CI 0.71–0.91).Conclusion We conclude that CT and US had comparable, moderate accuracy in diagnosing CP. Neither modality had high enough sensitivity to exclude the diagnosis as a standalone method.
Keywords: chronic pancreatitis; CT; pancreas; pancreatitis; ultrasound